Acid-catalysed reactions between methanol and the bio-oil from the fast pyrolysisof mallee bark - Hu, Xun; Gunawan, Richard; Mourant, Daniel; Lievens, Caroline; Li, X.; Zhang, Shu; Chaiwat, Weerawut; Li, Chun-Zhu (Elsevier Science Ltd, 2012)
This paper reports the acid-catalysed reactions between methanol and the bio-oil from the fast pyrolysis of mallee bark. The study focused on the reactions of the fatty acids, esters, furans and anhydrosugars in the bio-oil with methanol at 70–170 °C in the presence of a solid acid catalyst Amberlyst 70. Under the experimental conditions employed, both simple acids and fatty acids in bio-oil could be converted to either methyl esters or lactone, respectively. High molar mass esters in the original bio-oil tend to undergo transesterification to produce methyl esters. Furan aldehydes such as furfural and 5-methyl-2-furancarboxaldehyde mainly underwent acetalisation to their acetals, while 5-(hydroxymethyl)furfural (HMF) could undergo acetalisation and/or etherification. HMF including its ethers and acetals could be further converted into methyl levulinate at elevated temperatures. In addition, methyl levulinate was also found to be the product from the methanolysis of other furans such as 2-furylmethanol and the C6 anhydrosugars in bio-oil.